China and globalization in the Amazon - Brito, Cleiton Maciel, author.
1 online resource (xx, 122 pages)
Keywords: "China and Globalization in the Amazon examines Chinese investment in the Global South, with particular attention to industrial activity in Latin America. Based on ethnographic work conducted in several Chinese factories in the Amazon region of Brazil, whether private, partially private or state-owned, it explores the impact of these factories on the lives of workers, specifically on wages, laws and labour benefits, as well as the relationship between management and workers. A study of Chinese globalisation and industrial expansion in the developing world, and the implications of the Chinese management model for workers - and their reactions - this volume will be of interest to scholars of the sociology of work and organisations, globalisation, development studies and politics"--